2016
DOI: 10.4049/jimmunol.1600915
|View full text |Cite
|
Sign up to set email alerts
|

Functional Differences between IgM and IgD Signaling in Chronic Lymphocytic Leukemia

Abstract: B-cell receptor (BCR) signaling is a central pathogenetic pathway in chronic lymphocytic leukemia (CLL). Most CLL cells express BCRs of IgM and IgD isotypes, but the contribution of these isotypes to functional responses remains incompletely defined. We therefore investigated differences between IgM and IgD signaling in freshly isolated peripheral blood CLL cells and in CLL cells cultured with nurselike cells (NLC), a model that mimics the lymph node microenvironment. IgM signaling induced prolonged activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 56 publications
(70 reference statements)
2
27
0
Order By: Relevance
“…Most CLL cells express IgM receptors that, upon stimulation, activate signaling via the BCR, BTK, ERK, and AKT kinases to favor survival. 29 Our results demonstrating the ability of HDAC inhibitors singly or in combination with ibrutinib to effectively target BTK protein and abrogate its downstream signaling under conditions of IgM stimulation highlight the utility of this combination to antagonize the BCR-mediated survival advantage. In addition, because HDAC inhibitors can effectively also target mutated BTK in vitro, trials of HDAC inhibitors in treating ibrutinib-resistant CLL would be a rational strategy for patients with ibrutinib-resistant disease because survival for this group of patients is extremely poor.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Most CLL cells express IgM receptors that, upon stimulation, activate signaling via the BCR, BTK, ERK, and AKT kinases to favor survival. 29 Our results demonstrating the ability of HDAC inhibitors singly or in combination with ibrutinib to effectively target BTK protein and abrogate its downstream signaling under conditions of IgM stimulation highlight the utility of this combination to antagonize the BCR-mediated survival advantage. In addition, because HDAC inhibitors can effectively also target mutated BTK in vitro, trials of HDAC inhibitors in treating ibrutinib-resistant CLL would be a rational strategy for patients with ibrutinib-resistant disease because survival for this group of patients is extremely poor.…”
Section: Discussionmentioning
confidence: 72%
“…Similar to cells exposed to abexinostat alone, there were time-dependent losses in p-PLCg2, p-ERK, and p-AKT, indicating the inhibition of BTK-mediated signaling ( Figure 5C). CLL cells respond to stimulation with IgM by activating BCR and BTK signaling to favor survival, 29 which was measured by increased p-ERK and p-AKT compared with their levels in unstimulated cells (supplemental Figure 5B). Exposure to ibrutinib inhibited p-BTK and For personal use only.…”
Section: Org Frommentioning
confidence: 99%
“…When the recently egressed and the persistently circulating fractions were identified by means of these markers, we observed that sIgM was higher in the recently egressed CLL cells. Interactions of CLL cells with tissue environmental cells will affect levels of functional BCR IgM/D complex (47). We and others have speculated that the higher sIgM might be a consequence of expression enhancement by tissue-derived IL4 (48,49).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, different BCR isotype stimulation played a role in B‐CLL. IgM signaling triggered B‐CLL cell survival via Erk activation, whereas IgD signaling induced phosphorylation of HS1 leading to BCR internalization and failure to induce B‐CLL cell survival . Thus, the type of BCR response may critically affect B‐CLL outcome which again involves HS1.…”
Section: Pathophysiologic Relevance Of Hs1mentioning
confidence: 99%